(untitled) (International journal of artificial intelligence, 2026)
The article highlights the importance of financial control in improving the accounting system of fixed assets in budgetary organizations. It analyzes the role of control in ensuring the efficient use of fixed assets, their proper accounting, and accurate reflection in financial statements.